Participatory organizational change in community-based health and human services: From tokenism to political engagement - Bess, K.; Prilleltensky, Issac; Perkins, D.; Collins, L. (Springer, 2009)
Community psychologists have long worked with community-based human service organizations to build participatory processes. These efforts largely aim at building participatory practices within the current individual-wellness paradigm of human services. To address collective wellness, human service organizations need to challenge their current paradigm, attend to the social justice needs of community, and engage community participation in a new way, and in doing so become more openly political. We use qualitative interviews, focus groups, organizational documents, and participant observation to present a comparative case study of two organizations involved in such a process through an action research project aimed at transforming the organizations' managerial and practice paradigm from one based on first-order, ameliorative change to one that promotes second-order, transformative change via strength-based approaches, primary prevention, empowerment and participation, and focuses on changing community conditions. Four participatory tensions or dialectics are discussed: passive versus active participation, partners versus clients, surplus powerlessness versus collective efficacy, and reflection/learning versus action/doing. © 2009 Springer Science+Business Media, LLC.